Targeting the microRNAs in exosome: A potential therapeutic strategy for alleviation of diabetes-related cardiovascular complication. (November 2021) - Zhao, Simin; Wang, Hengquan; Xu, Haiqiang; Tan, Yao; Zhang, Chi; Zeng, Qian; Liu, Lingyun; Qu, Shunlin
Abstract: Diabetes-related cardiovascular disease (CVD) is a global health issue that causes thousands of people's death around the world annually. Diabetes-related CVD is still prevailing despite the progression being made in its diagnosis and treatment. Therefore it is urgent to find therapeutic strategies. to prevent it. MicroRNA (miRNA) is a single-stranded non-coding RNA involved in the process of post-transcriptional control of gene expression in eukaryotes. A large number of literatures reveal that miRNAs are implicated in diabetes-related CVD. The increase of miRNAs in exosomes may promote the occurrence and development of diabetes-related cardiovascular complication. However, some other studies identify that miRNAs in exosomes are supposed to be involved in cardiac regeneration and confer cardiac protection effect. Therefore, targeting the miRNA in exosome is regarded as a potent therapeutic measure to alleviate diabetes-related CVD. In this article, we review current knowledge about the role of exosomal miRNAs in diabetes-related cardiovascular complication, such as coronary heart disease, Peripheral artery disease, stroke, diabetic cardiomyopathy, diabetic nephropathy and diabetic retinopathy. Exosomal miRNAs are considered to be central regulators of diabetes-Related CVD and provide a therapeutic tool for diagnosis and treatment of diabetes-related cardiovascular complication. Graphical Abstract: ga1